Dividend Policy Decisions: Theoretical Views and Relevant Issues - Panigrahi, Shrikant; Yuserrie, Zainuddin (Hikari Ltd., 2015)
This paper provides literature on dividend policy decisions by the corporates in the perspective of share holder's wealth.